THE DIFFICULTIES FACED BY UNDERGRADUATE STUDENTS OF ENGLISH LANGUAGE EDUCATION PROGRAM WHEN LEARNING “ICT IN ELT” IN ONLINE ENVIRONMENT - Nugrahani, Arina (Jurnal TAMBORA, 2025)
Our lives have been significantly impacted by information and communication technology (ICT) which is continuously growing. Due to the spread of COVID-19, many sectors have been forced to accelerate their technological innovation. It also has had a significant impact on education throughout the world and it aroused the use of e-learning which was previously seen as a complementary medium in the education process. English language education program is program that prepares and trains future teachers, and a course called "ICT in ELT" is offered to Undergraduate students in this study program so that they are capable of using a variety of instructional technologies in increasingly digital classrooms. This research aims to investigate the difficulties faced by Undergraduate students of English Language Education Program when learning “ICT in ELT” course using online learning method. Qualitative approach with case study research design is implemented in this study. The data collection process was conducted by observing three classes that taught “ICT in ELT” course and interviewing study participants. The study employs purposive sampling and five participants were selected from each class, and thus a total of 15 students chosen as the participants. The research findings show that there are a number of difficulties experienced during the e-learning process, namely: internet connection, comprehension, practice, gadget, learning media, time and learning target, discussion and interaction, regional infrastructure, creativity, and video quality. Meanwhile, the two factors that become the major issues in learning “ICT in ELT” are internet connection and comprehension problems.